Clinical Effects of Activated Charcoal Unavailability on Treatment Outcomes for Oral Drug Poisoned Patients - Park, Sohyun; Lee, Hui Jai; Shin, Jonghwan; You, Kyoung Min; Lee, Se Jong; Jung, Euigi (Emergency Medicine International, 2018)
Background. Activated charcoal is the most frequently and widely used oral decontaminating agent in emergency departments (EDs). However, there is some debate about its clinical benefits and risks. In Korea, activated charcoal with sorbitol was unavailable as of the mid-2015, and our hospital had been unable to use it from September 2015. This study examined the differences of clinical features and outcomes of patients during the periods charcoal was and was not available. Methods. We retrospectively reviewed the electronic medical records of patients who had visited an urban tertiary academic ED for oral drug poisoning between January 2013 and January 2017. Results. For the charcoal-available period, 413 patients were identified and for the charcoal-unavailable period, 221. Activated charcoal was used in the treatment of 141 patients (34%) during the available period. The mortality rates during the available and unavailable periods were 1.9 and 0.9%, respectively (p = 0.507). There was also no interperiod difference in the development of aspiration pneumonia (9.9 versus 9.5%, p = 0.864), the endotracheal intubation rate (8.4 versus 7.2%, p = 0.586), and vasopressor use (5.3 versus 5.0%, p = 0.85). Intensive care unit (ICU) admission was higher in the unavailable period (5.8 versus 13.6%, p = 0.001). ICU days were lower in the unavailable period (10 [4.5-19] versus 4 [3-9], p = 0.01). Hospital admission (43.3 versus 29.9%, p = 0.001) was lower in the unavailable period. Conclusions. In this single center study, there appeared to be no difference in mortality, intubation rates, or vasopressor use between the charcoal-available and charcoal-unavailable periods.